Parâmetros cinéticos e termodinâmicos da adsorção do alaranjado de metila por hidróxidos triplos lamelares obtidos a partir do rejeito de bauxita - Lima, Ronária Silva (2024)
In this study, waste from bauxite beneficiation was used, obtained by acid leaching, of which 200 g of waste was used, obtaining 20 g of leached material, which corresponds to a yield of 10%. This material obtained in leaching, with a predominance of Al2O3 (20.95%) and Fe2O3 (5.27%), was used in the synthesis of layered triple hydroxides (LTHs), as trivalent metals, being structurally compared with the HTL [Co-Al-Fe-Cl]REFERENCE, both synthesized at a constant pH of 8.0 ± 0.5. Therefore, the objective of this work was to synthesize and characterize layered triple hydroxides (LTHs) of the [Co-Al-Fe-Cl] type from bauxite tailings obtained from the ALCOA mining company located in Juriti, Pará state, and to use them as adsorbents for the azo dye methyl orange. In the X-ray diffractograms of the HTLs [Co-Al-Fe-Cl]REFERENCE and [Co-Al-Fe-Cl]REJECT, well-defined diffraction peaks indexed to rhombohedral symmetry, space group R(-3) similar to the hydrotalcite-type structure were observed. The adsorption tests were performed with a 10 mg L-1 dye solution, 50 mL volume with different adsorbent masses (10, 15 and 20 mg) at pH 7.0 ± 0.5 and pH 5.0 ± 0.5 at 23°C. The results were adjusted to pseudo-first and second order kinetic models. In the contact time tests for HTLREFERENCE, masses of 10, 15 and 20 mg were used at pH 7.0 ± 0.5 and 23.41; 24.79 and 20.96 mg g-1 were obtained in 120; 100 and 40 min, respectively. For HTLREJECT, 10 and 15 mg were used and 45.57 and 33.05 mg g-1 of adsorptive capacity were obtained in 30 and 16 min, respectively. In the isothermal tests at temperatures (293, 303, 313 and 323 K), it was observed that HTLREFERENCE adjusted to the Langmuir isotherm, indicating chemical adsorption, while HTLREJECT adjusted to the Freundlich isotherm, indicating physical adsorption. In the Langmuir isotherms, the maximum adsorptive capacity values were obtained and increased with increasing temperature. The ΔG° values were lower than 0, indicating a spontaneous adsorption process. In the thermodynamic study of both HTLs, ΔH° magnitudes lower than 25 KJ mol-1 were obtained, suggesting a predominantly physical adsorption for both HTLs and negative ΔS° values indicating a decrease in adsorbate/adsorbent randomness in the adsorption process. Therefore, HTL [Co-Al-Fe-Cl], synthesized from metals obtained from bauxite beneficiation by the co-precipitation method at constant pH, is a promising alternative both in the recovery of bauxite waste and in the adsorption of methyl orange present in contaminated waters.